ANALISIS GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KINERJA DI INSTALASI RAWAT INAP DI RS. BAPTIS KEDIRI - Yusuf Yudi Sasmito; Eka Askafi (Universitas Islam Kadiri, 2020)
The nurse is one of the main components in providing health care to the patient , the presence of nurses providing more value than a treatment , so that patients do not just get the health care that are holistic . The purpose of this study is to examine and determine the direct effect of leadership style on performance, to test and determine indirect influence of leadership style on performance through job satisfaction , and to examine and determine the direct effect of job satisfaction on performance.The hypothesis of this study leadership style through job satisfaction of nurses affect the performance , leadership style directly affects the performance of nurses , and job satisfaction directly influence the performance . Respondents for this study as many as 180 people , because the population is already known, the method of data collection using census methods and to answer this hypothesis , a number of analytical tools have been used by the analysis tool that analyzes the path . The author uses the path analysis.From the results of the analysis carried out can be concluded that the first hypothesis that the style of leadership through job satisfaction has positive influence on employee performance is proven, the second hypothesis leadership style direct positive effect on the performance of nurses proved, to the satisfaction of three direct positive effect on the performance of nurses